Insights into intermetallic phases on pulse welded dissimilar metal joints - Beyer, E.; Brenner, B.; Göbel, G.; Herrmannsdörfer, T.; Kaspar, J. (Institut für Umformtechnik - Technische Universität Dortmund, 2010)
The Magnetic Pulse Welding (MPW) process has been developed to an industrially used joining method which is considered to be a fast, noncontact, clean and "cold" solid state welding process. Unlike fusion welding, the absence of direct heat during the welding cycle makes it possible to join dissimilar metals, for instance aluminium to copper or copper to steel, without noticeable detrimental metallurgical defects. This is very desirable, as today s industry lacks technologies to join often not fusion-weldable dissimilar materials effectively. However, current metallographic studies show that for many material combinations the formation of intermetallic seams in the joint region of magnetic pulse welds can not be completely avoided. Modern technical equipment for MPW is used to join aluminium with copper in order to study the microstructure and the intermetallic phases formed in the weld region in dependence of the processing parameters. The welds are analysed by means of metallographic and electron microscopic (SEM) methods. Relations between the parameters and the microstructures formed within the weld joints are shown. Based on the obtained results conclusions will be drawn with respect to the intermetallic phase formation process and the optimization of the weld microstructure and properties.
Keywords: analysis; interface; welding; 620; 670